Monotonic and fatigue properties of kenaf /glass hybrid composites under fully reversed cyclic loading - Sharba, Mohaiman Jaffar; Leman, Zulkiflle; Hameed Sultan, Mohamed Thariq; Ishak, Mohamad Ridzwan; Mohamed Ariff, Azmah Hanim (IOP Publishing, 2015)
The aim of this work is to investigate the effect of hybridization of kenaf-glass fibers reinforced unsaturated polyester on fatigue life. Three types of composites were fabricated using hands lay-up method, namely, kenaf, glass, and hybrid composites with 30% of weight fraction, the hybrid was mixed with a ratio of kenaf: glass 10:20. Monotonic tests were achieved (Tensile and compression) to determine the fatigue stress levels. Fully reversed fatigue loading was conducted with a stress ratio of -1 and stress levels 55-85% of the ultimate static stresses, all tests were conducted at 10 Hz of frequency. The results proof a positive hybrid composite; also agree with the rule of mixture that can predict the final composite properties. Moreover, it's been observed an improvement in overall mechanical properties of hybrid compared to individual ones.